Óleos essenciais na indução de resistência em morangos ao mofo cinzento, à botrytis cinerea in vitro e ação toxicológica - Vismara, Lilian de Souza (2019)
The present work aims to present studies on the efect of essential oils (EOs) of citronella (Cymbopogon sp. Spreng.), guaçatonga (Casearia sylvestris Sw.), melaleuca (Melaleuca sp. L.), patchouli (Pogostemon sp. Benth.) and pitangueira (Eugenia uniflora L.) in the induction of resistance in strawberries [Fragaria ananassa (Weston) Rozier] cv. Caminho Real to the gray mold at postharvest in vivo, in the control of Botrytis cinerea Pers.:Fr in vitro and in bioassays of toxicity of the EOs to the nauplii of Artemia Salina L. and embryos of Gallus Gallus domesticus L. in egg. As expected to point out perspectives for the use of mathematicalstatistical modeling tools for data programming in the collaborative environment R. For this, from 2016 to 2019, five studies were carried out as follows: STUDY I – Essential Oils (EOs); STUDY II – Characterization of the isolate of Botrytis cinerea; STUDY III – Application of the logistic growth model [Verhulst] and sensitivity tests in vitro of B. cinerea to EOs; STUDY IV – Induction of resistance in strawberries cv. Caminho Real to gray mold in post-harvest and STUDY V – Generalized linear models (GLMs) and the toxicological action of the EOs. The mass density obtained from diferent EOs is consistent with values presented in normatives, which allows us to arm that the steam extraction process was adequate and the oils with which we developed this research, have purity and quality. The cromatographic studies with the diferent EOs demonstrated that there is a specificity in relation to the active ingredients and a high diversity of compounds. And, when working with a diversity, the synergistic potential of the substances is explored; however, it opens up the possibility for specific studies considering the fractionation of oils. The morphological characterization associating optical microscopy with scanning electron is adequate to characterize B. cinerea. The Doyle-Doyle method for extraction of DNA from the mycelium of B. cinerea resulted in a suffcient amount of material for subsequent sequencing. GenBankR and BLASTTM were tools that favored molecular identification by similarity. The best temperature for the development of the isolate was 20 °C. The logistic growth model [Verhulst] allowed to describe the mycelial growth of B. cinerea in vitro (Ø, mm), where the interpretation of the parameters has biological explanation regarding kinematics under conditions of fungal growth in closed system. The sensitivity tests of B. cinerea to EOs, by the methods [of mycelial growth] disk difusion and microdilution in broth showed that all the evaluated EOs had potential in the control of B. cinerea, having specificity in relation to oil and concentrations; with emphasis on the citronella and melaleuca EOs that presented volatile dose and concentration fungicides. The use of EOs by volatilization in strawberry fruits led to less development of postharvest rot and reduced mass loss; not interfering in the parameters related to staining and acidity. The activated defense mechanisms presented specificity as a function of the oils, which acted in two ways: route of the phenolpropanoids with activation of the PAL and in the formation of PR-proteins, specifically the 1;3 glucanase. In relation to ecotoxicity, the mean lethal concentration, CL50, of the EOs to the nauplii of A. salina ranged from 1.49 to 5.7 µg mL1; where pitangueira and citronella were the less toxic. For the synthetic fungicide based on iprodione, at the recommended concentration for the control of gray mold in strawberries, the mortality of this bioindicator was 100%. The concentrations of all the test products (EOs and synthetic fungicide) maintained the survival of embryos of G. Gallus domesticus in egg above 50%. Moreover, the embryonic viability was not influenced by the treatments, as well as the percentages of survival, normal embryonic formation and there was also no lag and/or acceleration of embryonic development due to the products tested. Therefore, the studied EOs may be applied as phytosanitary control agents to B. cinerea. Thus, the information presented here allows adequate management of the synergistic action of its active compounds also on parameters related to toxicological action in an agroECOsystem. Futhermore, it is hoped that this work will serve to point out an overview for the use of these EOs also in other pathosystems of interest for Plant Production.